Structural validation of a brief, multidimensional measure of psychological flexibility and inflexibility in adolescence - Langenskiöld, Jakob; Räsänen, Pekka; Adhikary, Prince Das; Salmela, Rosa; Laakso, Mikko-Jussi; Alanko, Katarina (Springer Science and Business Media LLC, 2026)
Background:
Psychological flexibility and inflexibility (PF/PI) are increasingly targeted in clinical and preventive interventions as processes relevant to both flourishing and distress. However, brief multidimensional measures that assess both constructs and are developmentally appropriate for children and younger adolescents remain scarce. This study investigated the dimensionality of PF/PI in early and mid-adolescence, and conducted a preliminary structural validation of a brief questionnaire for potential use in school settings.
Methods:
Data were drawn from a cross-sectional sample of 1,289 Finnish lower secondary school students in grades six, eight, and nine. Eighteen items adapted from the Children’s Psychological Flexibility Questionnaire (CPFQ) were administered before a digital mathematics assessment. Both exploratory (EFA) and confirmatory factor analysis (CFA) with tests of measurement invariance were conducted using a split sample approach. Internal consistency was evaluated using alpha and omega coefficients, and average inter-item correlations.
Results:
The iterative item retention process resulted in a three-factor nine-item solution (CPFQ-9) that met predefined psychometric criteria and was replicated with CFA. The model included two modestly correlated PF factors (1) committed action with awareness, 2) acceptance and defusion) and one largely independent PI factor (3) self-judgment and fusion). Configural, metric and partial scalar invariance were supported across grade and gender. Subscale internal consistency were questionable to borderline acceptable but average inter-item correlations were within recommended ranged for shorter scales.
Conclusions:
Findings suggest that a brief, multidimensional measure can capture developmentally relevant flexibility- and inflexibility-related processes in early and mid-adolescence. Further work is needed to establish convergent, divergent, and predictive validity, test-retest reliability, and applicability in younger age groups and contexts, before the CPFQ-9 can be considered a robustly validated, developmentally sensitive measure.